Mechanical properties and long-term stability of novel lipid formulations with simvastatin - Ćetković, Zora; Vasiljević, Ivana; Cvijić, Sandra; Vasiljević, Dragana (Archives of Pharmacy, 2022)
Mixing selected liquid SMEDDS with polymethacrylate polymers (Eudragit®) led to solidification of the samples to form solid, ductile, transparent systems. The purpose of this study was to define mechanical properties and long-term stability of novel simvastatin-loaded SMEDDS-based drug delivery systems. SMEDDS-based formulations were prepared by adding liquid SMEDDS (10% oleoyl macrogol-6 glycerides and 90% caprylocaproyl macrogol-8 glycerides/macrogol-15-hydroxystearate, in 3 ratios: 1:1, 2:1 and 3:1) to Eudragit® S100 or Eudragit® S100/Eudragit® L100 combination (in 1:1 ratio), until SMEDDS/polymer ratio 2:1 w/w was reached. SMEDDS-based formulations with simvastatin (SV) were prepared by dissolving SV (5%) into liquid SMEDDS and mixing with polymethacrylate polymers in the same ratio. Prepared formulations were evaluated in terms of their mechanical properties and long-term stability. The results indicated that the increase in the caprylocaproyl macrogol-8 glycerides concentration resulted in higher penetration force (F1 S100–F3 S100 = 5.83-7.22 N and F1 SL100-F3 SL100 = 4.20-5.99 N). However, addition of SV was negatively correlated with the hardness, i.e. samples with SV were softer in comparison to unloaded samples. Moreover, it was noticeable that formulations with Eudragit® S100 had greater penetration force values compared to formulations containing Eudragit® S100/Eudragit® L100. After six months of storage at room and elevated temperature, only slight decrease in SV content (less than 5%) was observed in these samples. This study demonstrated that novel SMEDDS-based formulations with higher concentration of caprylocaproyl macrogol-8 glycerides and those with Eudragit® S100 were more robust, which may further serve as a guide for formulating tailor-made formulations.